2009 International Conference on Education Technology and Computer 2009
DOI: 10.1109/icetc.2009.37
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on Students' Acceptance of Writing Web Logs: A Test of Technology Acceptance Model

Abstract: The application of computer in education is on the rise recently. However, using web logs in English Language Teaching (ELT) is rather new in Malaysia since the students' acceptance of writing web logs has not been extensively examined in previous studies. Therefore, the objective of this study is to measure students' acceptance of writing web logs employing the Davis' Technology Acceptance Model (TAM). Two determinants-Perceived Ease of Use (PEOU) andPerceived Usefulness (PU) are used to determine an individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…As pointed out by Othman and Amiruddin (2010), students may benefit from multimedia presentation based on a Visual/Auditory, Reading/Writing, Kinaesthetic (VARK) learning style that allows them to learn through a range of activities that increase cognitive activity and motivation. With regard to accommodating a range of learning styles, the experiential learning opportunities characteristic of CALL may be of particular benefit to low-proficiency EFL learners (Yih, 2009), who may be offered opportunities to interact with peers in the virtual classroom with the scaffolding of new knowledge through collaborative activities. Heift (2004), for example, reported that the feedback learners received during such activities served as the basis for their scaffolding of new knowledge, and was found to be significantly correlated to their uptake of CALL.…”
Section: Discussionmentioning
confidence: 99%
“…As pointed out by Othman and Amiruddin (2010), students may benefit from multimedia presentation based on a Visual/Auditory, Reading/Writing, Kinaesthetic (VARK) learning style that allows them to learn through a range of activities that increase cognitive activity and motivation. With regard to accommodating a range of learning styles, the experiential learning opportunities characteristic of CALL may be of particular benefit to low-proficiency EFL learners (Yih, 2009), who may be offered opportunities to interact with peers in the virtual classroom with the scaffolding of new knowledge through collaborative activities. Heift (2004), for example, reported that the feedback learners received during such activities served as the basis for their scaffolding of new knowledge, and was found to be significantly correlated to their uptake of CALL.…”
Section: Discussionmentioning
confidence: 99%
“…Y. Lee & Lehto, 2013;H. Li, 2013;Mah, 2009;Saeed, Yang, & Sinnappan, 2009;Sekhaolelo & Kalema, 2015;Tajuddin, Mustapha, Zaini, & Aziz, 2012;Thongmak, 2011Thongmak, , 2014 The increasing number of studies on the behavioral aspects toward technology usage has resulted in several models that address the individuals' acceptance or rejection of a specific technology (Ajzen, 1991;Davis, 1989;Venkatesh, Morris, Davis, & Davis, 2003). With respect to the IS theories/models that were used to study the social media acceptance and adoption, the analysis results are illustrated in Table 3.…”
Section: Rq1 To What Extent Does the Literature Tackle The Social Mementioning
confidence: 99%